The final hour : the last Homelanders novel / Andrew Klavan - Klavan, Andrew
Time is short, but eighteen-year-old Charlie West has one last chance to stop the Homelanders from attacking when he finally gets back enough of his memory to realize when the terrorists are going to strike next.